Malignant risk of pelvic mass after hysterectomy for adenomyosis or endometriosis. Issue 15 (April 2020) - Chao, Xiaopei; Liu, Yang; Ji, Mingliang; Wang, Shu; Shi, Honghui; Fan, Qingbo; Lang, Jinghe
Abstract : Abstract: Pelvic mass onset following a hysterectomy due to benign disease is not rarely seen. Appropriate diagnosis and treatment are of great importance. This study aims to analyze the clinicopathological features of patients who have received surgery for pelvic mass following hysterectomy due to gynecological benign disease, especially endometriosis or adenomyosis. This study retrospectively analyzed the patients undergone reoperation for pelvic mass subsequently to hysterectomy from January 2012 to December 2016 in a tertiary teaching hospital. A total of 247 patients were enrolled in this study. There is a significant difference between the patients with or without a history of endometriosis/adenomyosis. Multivariate analysis showed that the pelvic mass had a higher risk of being ovarian endometrioid carcinoma, ovarian clear cell carcinoma, ovarian endometriosis, and ovarian physiological cysts in patients with a history of adenomyosis/endometriosis. The pathology of the subsequent pelvic mass inclines to be benign, includes ovarian endometriosis, ovarian physiological cysts, and pelvic encapsulated effusion. Postoperative adjuvant therapy for those received hysterectomy due to endometriosis/adenomyosis, like gonadotropin releasing hormone agonists (GnRHa), may contribute to the prevention of benign pelvic mass. Patients with a history of hysterectomy due to endometrisos/adenomyosis tend to have a shorter time interval between hysterectomy and pelvic malignant tumors onset. Abstract : Supplemental Digital Content is available in the text